Extraction of squalene from palm oil mesocarp using supercritical carbon dioxide - Chen, Xiao Long (2014)
An innovative technique of Supercritical Fluid Extraction (SFE) process was adopted for the extraction of squalene from palm oil mesocarp. SFE is the process of separating the extractant from components using supercritical fluids (SCF) with CO2 as the extracting solvent. However, the use of SFE for industrial application is still unpopular and the references of SFE are serious shortage in present. In this study, there was a comparison experiment between SC-CO2 extraction and Soxhlet extraction in order to investigate the better method to extract squalene. Meanwhile, for SC-CO2 extraction, the task was investigated the influence of independent conditions of pressure, temperature and CO2 flow rate on the extraction of squalene and these independent variables were selected as follows: temperature (45-75 ?), pressure (16-30 MPa) and CO2 flow rate (2-5 ml/min). Afterwards, the chemical compositions of palm oil were analyzed by gas chromatography-mass spectrometry (GC-MS). Furthermore, the conditions of SC-CO2 extraction for squalene were optimized by response surface methodology (RSM) following Box-Behnken Design (BBD) and the result was analyzed by Design Expert software. In the end, the optimum conditions obtained from the investigation were pressure (16 MPa), temperature (45.01 ?) and CO2 flow rate (2 ml/min) and the yield of squalene was 0.506%. Besides, after compared the yield of squalene, the method of SC-CO2 extraction was better than the conventional Soxhlet extraction.